The first example of the two‐electron reduction of a phosphaalkyne – synthesis and structural characterisation of the diuranium(IV) pentalene complex [(U{η5‐C5Me5}{η8‐C8H4(SiiPr3‐1,4)2})2(μ‐η2:η1‐tBuCP)] - Tsoureas, N; Kilpatrick, A; Summerscales, OT; Nixon, JF; Cloke, FGN; Hitchcock, PB (Wiley, 2013)
The facile two‐electron reduction of the phosphaalkyne tBuC≡P by the UIII cyclopentadienyl–pentalene mixed‐sandwich complex [U(η5‐C5Me5){η8‐C8H4(SiiPr3)2}] is reported. A single‐crystal X‐ray structural analysis of the diuranium(IV) product [(U{η5‐C5Me5}{η8‐C8H4(SiiPr3)2})2(μ‐tBuCP)] shows that it contains a slightly unsymmetrical, bridging μ‐η2:η1‐ligated phosphaalkene dianion.